Wireless Body Area Network Transmission Model Based on Measurement Data - Chaisang, Aditep; Promwong, Sathaporn (My University, 2018)
Wireless body area network (BAN) technology is becoming an increasingly important part of the human body communication system and short range applications. Characteristic of ultra wideband impulse radio (UWB-IR) channel propagation is very important. The human body is more complex than other applications. Therefore, to understand the characteristics of the channel distribution on the human body is so important. This paper presents characteristic of channel propagation due to effect within human body and without human body for wireless applications based on measurement data. The template waveform is considered at the receiver side to maximize the SNR for evaluation. In this paper, the results are evaluated based on the extended Friis' transmission formula. This technique gives very accurate results and is very useful for the design and evaluation of UWB transmission for wireless medical applications, especially focusing on the effect of template waveform.
Keywords: Friis's transmission formula; UWB; UWB antenna; UWB-IR; WBAN